UAV deployment and channel allocation considering diverse QoS constraints and service importance. (3rd August 2021) - Liu, Cuntao; Zhao, Wendong
The deployment of unmanned aerial vehicle (UAV) as well as the allocation of channels is important for satisfying users' differentiated information transmission demand in UAV-enabled communication. With diverse quality of service (QoS) requirements and users' service importance considered simultaneously, a joint optimisation problem of UAV deployment and channel allocation is proposed. The maximisation of service-importance weighted system capacity on the premise of maximising the number of users served simultaneously, is taken as the optimisation objective. A rapid hybrid algorithm combined greedy algorithm and swarm intelligence optimisation algorithm is then proposed to solve this problem. Simulation results show that the weighted average capacity obtained based on our algorithm is about 10.4% higher than that without considering service importance at a tiny cost of unweighted capacity, while maximising the number of users accessing the channels.